Avaliação da atenção primária em Sapucaia do Sul: comparação entre o modelo tradicional e a estratégia saúde da família - Chazan, Cassiane Prestes da Silveira (Universidade do Vale do Rio dos Sinos, 2017)
Almost 40 years after the International Conference on Primary Health Care (Alma–Ata), the development and consolidation of primary health care (PHC) has gained the status of priority strategy to ensure the reduction of health inequities around the world . (WHO; UNICEF, 1978; OLIVEIRA, 2007). In Brazil, with the establishment of the Unified Health System (SUS) from the Federal Constitution of 1988, health was defined as a duty of the state and a right for all. Thus, the concern with access, care coordination, integrality, longitudinality and popular participation were consolidated day by day through the strengthening and expansion of PHC. (BRASIL, 2003a). In 1994, the Community Health Agents Program (PACS) was created, later expanded to the Family Health Program and institutionalized as the Family Health Strategy (ESF), which became the government's priority agenda for primary care.
Keywords: Cuidados primários de saúde; Saúde pública; Medicina da família; Primary health care; Public health; Family medicine; ACCNPQ::Ciências da Saúde::Saúde Coletiva